Electrolyte and mineral disturbances in septic acute kidney injury patients undergoing continuous renal replacement therapy. Issue 36 (September 2016) - Jung, Su-Young; Kim, Hyunwook; Park, Seohyun; Jhee, Jong Hyun; Yun, Hae-Ryong; Kim, Hyoungnae; Kee, Youn Kyung; Yoon, Chang-Yun; Oh, Hyung Jung; Chang, Tae Ik; Park, Jung Tak; Yoo, Tae-Hyun; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Electrolyte and mineral disturbances remain a major concern in patients undergoing continuous renal replacement therapy (CRRT); however, it is not clear whether those imbalances are associated with adverse outcomes in patients with septic acute kidney injury (AKI) undergoing CRRT. We conducted a post-hoc analysis of data from a prospective randomized controlled trial. A total of 210 patients with a mean age of 62.2 years (136 [64.8%] males) in 2 hospitals were enrolled. Levels of sodium, potassium, calcium, and phosphate measured before (0 hour) and 24 hours after CRRT initiation. Before starting CRRT, at least 1 deficiency and excess in electrolytes or minerals were observed in 126 (60.0%) and 188 (67.6%) patients, respectively. The excess in these parameters was greatly improved, whereas hypokalemia and hypophosphatemia became more prevalent at 24 hours after CRRT. However, 1 and 2 or more deficiencies in those parameters at the 2 time points were not associated with mortality. However, during 28 days, 89 (71.2%) deaths occurred in patients with phosphate levels at 0 hour of ≥4.5 mg/dL as compared with 49 (57.6%) in patients with phosphate levels <4.5 mg/dL. The 90-day mortality was also significantly higher in patients with hyperphosphatemia. Similarly, in 184 patients who survived at 24 hours after CRRT, hyperphosphatemia conferred a 2.2-fold and 2.6-fold increased risk of 28- and 90-day mortality, respectively. The results remained unaltered when the serum phosphate level was analyzed as a continuous variable. Electrolyte and mineral disturbances are common, and hyperphosphatemia may predict poor prognosis in septic AKI patients undergoing CRRT.